Legal Help in International Criminal Procedure Law - L. A. Lazutin (Московский журнал международного права, 2008)
The issue of international criminal process has been analyzed by scholars before the revolution in Russia took place. From that time there still goes on the discussion whether the criminal procedure law should be recognized as a branch of international law. There exist several points of view on this subject which are enumerated in the article. Discussion as to the place o international criminal procedure law is still continuing.International legal process is a composite part of international process as a whole and is an institute of international criminal law. Several opinions of prominent scholars are given to support different approaches to this problem. The conclusion is that international criminal law and international criminal process compliment each other as they have the same goal.Further on the sources of international criminal law are analyzed which are divided into three groups. Then the author tries to prove the independent nature of international criminal procedure law and lists the relevant circumstances.But the main task the author sees is in locating the right place in international criminal procedure law for the institute of legal help in criminal cases.The last part is devoted to this particular question. One of the conclusions the author makes is that this institute is to be recognized as comprehensive and complex institute of international criminal procedure law.